Altered H19/miR‐675 expression in skeletal muscle is associated with low muscle mass in community‐dwelling older adults. Issue 2 (15th June 2021) - Antoun, Elie; Migliavacca, Eugenia; Garratt, Emma S; Barton, Sheila J; Titcombe, Phil; Westbury, Leo D; Baczynska, Alica; Dodds, Richards; Roberts, Helen C; Sayer, Avan A; Shaw, Sarah; Syddall, H.E.; et al.
Abstract: Background: Despite increasing knowledge of the pathogenesis of muscle ageing, the molecular mechanisms are poorly understood. Based on an expression analysis of muscle biopsies from older Caucasian men, we undertook an in‐depth analysis of the expression of the long non‐coding RNA, H19, to identify molecular mechanisms that may contribute to the loss of muscle mass with age. Methods: We carried out transcriptome analysis of vastus lateralis muscle biopsies from 40 healthy Caucasian men aged 68–76 years from the Hertfordshire Sarcopenia Study (HSS) with respect to appendicular lean mass adjusted for height (ALMi). Validation and replication was carried out using qRT‐PCR in 130 independent male and female participants aged 73–83 years recruited into an extension of the HSS (HSSe). DNA methylation was assessed using pyrosequencing. Results: Lower ALMi was associated with higher muscle H19 expression ( r 2 = 0.177, P < 0.001). The microRNAs, miR‐675‐5p/3p encoded by exon 1 of H19, were positively correlated with H19 expression (Pearson r = 0.192 and 0.182, respectively, P < 0.03), and miR‐675‐5p expression negatively associated with ALMi ( r 2 = 0.629, P = 0.005). The methylation of CpGs within the H19 imprinting control region (ICR) were negatively correlated with H19 expression (Pearson r = −0.211 to −0.245, P ≤ 0.05). Moreover, RNA and protein levels of SMAD1 and 5, targets of miR‐675‐3p, were negatively associated with miR‐675‐3p ( r 2 = 0.792 and 0.760, respectively) and miR‐675‐5p ( r 2 = 0.584 and 0.723, respectively) expression, and SMAD1 and 5 RNA levels positively associated with greater type II fibre size ( r 2 = 0.184 and 0.246, respectively, P < 0.05). Conclusions: Increased expression profiles of H19/miR‐675‐5p/3p and lower expression of the anabolic SMAD1/5 effectors of bone morphogenetic protein (BMP) signalling are associated with low muscle mass in older individuals.